2018
DOI: 10.1177/1071100718779393
|View full text |Cite|
|
Sign up to set email alerts
|

Diagnosis: History, Physical Examination, Imaging, and Arthroscopy: Proceedings of the International Consensus Meeting on Cartilage Repair of the Ankle

Abstract: This international consensus derived from leaders in the field will assist clinicians in the diagnosis of cartilage injuries of the ankle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 16 publications
2
19
0
Order By: Relevance
“…Studies have used the 9-grid scheme to determine the prevalence of different OLT locations, and there is strong consensus among the orthopedic community for this grid scheme. 6,18,26 Our study further supports the literature that kappa values can be used in the orthopedic and radiology communities to validate radiographic analysis of different osseous or cartilaginous lesions in the extremities. 3,5,9 Furthermore, many studies have found MRI accurate and superior to other imaging studies when diagnosing OLTs as this imaging modality is better at evaluating the overlying cartilage.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Studies have used the 9-grid scheme to determine the prevalence of different OLT locations, and there is strong consensus among the orthopedic community for this grid scheme. 6,18,26 Our study further supports the literature that kappa values can be used in the orthopedic and radiology communities to validate radiographic analysis of different osseous or cartilaginous lesions in the extremities. 3,5,9 Furthermore, many studies have found MRI accurate and superior to other imaging studies when diagnosing OLTs as this imaging modality is better at evaluating the overlying cartilage.…”
Section: Discussionsupporting
confidence: 82%
“…This method is gaining popularity with surgeons from the International Consensus Meeting on Cartilage Repair of the Ankle, stating there was a strong consensus for its utility within the orthopedic community. 26 Furthermore, it has been used in both basic science and clinical research. 12,18 However, there has been no study to evaluate its validity within the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Up to date, there is no consensus in the literature with regard to optimal images and tests to request in patients with suspected ankle cartilage injury, as well as with regard to specific imaging protocols that should be used. Furthermore, no study has examined the relationship between the results of preoperative imaging scans and operative findings (5) .…”
Section: Discussionmentioning
confidence: 99%
“…Cartilage injuries were confirmed by preoperative MRI, arthroscopic examinations and intraoperative measurement; outerbridge grading was performed by senior surgeons 43 44. Synovial fluid was aspirated during surgery and sent for laboratory examination.…”
Section: Methodsmentioning
confidence: 99%